2014
DOI: 10.1007/s40095-014-0112-6
|View full text |Cite
|
Sign up to set email alerts
|

Porosity of expanded clay manufactured with addition of sludge from the brewing industry

Abstract: This study describes the industrial use of waste generated from the brewing industry, specifically sludge from a wastewater treatment plant. The processing technique was developed to produce ceramic material with the potential for use as a lightweight aggregate in construction. This waste is usually dumped in landfills, but the current increase in restrictions on dumping and interest in improving the environment make our proposal for gaining value from this sludge a significant contribution. The chemical compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…This can be related to the porous structure of both materials. Expanded clay materials are well known for its mesoporous structure [54], which allows better results.…”
Section: Ibuprofen and Paracetamol Removal Performance By Activated Sludge And Comparison With Adsorption Processesmentioning
confidence: 99%
“…This can be related to the porous structure of both materials. Expanded clay materials are well known for its mesoporous structure [54], which allows better results.…”
Section: Ibuprofen and Paracetamol Removal Performance By Activated Sludge And Comparison With Adsorption Processesmentioning
confidence: 99%
“…The production of bricks with SSA involves the usual steps of mixing, molding, drying, and firing, using SSA as a substitute for clay or some of the other additives (e.g., sand or sawdust). The present research [32,[36][37][38] has shown justification for the production of bricks with added SS/SSA (maximum of 25 wt%), even though the results also differ between different authors indicating that results are influenced by the sludge origin, sludge treatment method, and the conditions used to generate the SSA.…”
Section: Introductionmentioning
confidence: 60%
“…Currently, the converting of industrial or biomass wastes into useful products, with maintaining the quality requirements at low cost and environmental impact, became a challenge for the production of building materials. Thus, the embedding of different types of wastes in the structure of building materials with sound and thermal insulating properties has been reported in many research studies [12][13][14][15][16][17]. A large field of natural materials is known as quickly renewable raw materials added as appropriate components to obtain the lightweight composite materials with application in building, such as sound or thermal insulators.…”
Section: Introductionmentioning
confidence: 99%